Vă rog să mă ajutați la acest exercițiu :
Anexe:
Răspunsuri la întrebare
Răspuns de
1
................................
Anexe:
Răspuns de
1
(2a-b)^2 + (2b+a)^2 = 5
(2a)^2 - 2×2ab + b^2 + (2b)^2 +2×2ba+a^2 = 5
4a^2 - 4ab +b^2 + 4b^2+4ab+a^2 = 5
4a^2 +a^2+4b^2+b^2 =5
5a^2+ 5b^2 = 5 |:5
a^2 + b^2 = 1
(2a)^2 - 2×2ab + b^2 + (2b)^2 +2×2ba+a^2 = 5
4a^2 - 4ab +b^2 + 4b^2+4ab+a^2 = 5
4a^2 +a^2+4b^2+b^2 =5
5a^2+ 5b^2 = 5 |:5
a^2 + b^2 = 1
Alte întrebări interesante
Engleza,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă